2021
DOI: 10.3390/ani11123572
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Music on Livestock: Cattle, Poultry and Pigs

Abstract: The welfare of animals, especially those kept in intensive production systems, is a priority for modern agriculture. This stems from the desire to keep animals healthy, to obtain a good-quality final product, and to meet the demands of today’s consumers, who have been increasingly persuaded to buy organic products. As a result, new sound-based methods have been pursued to reduce external stress in livestock. Music therapy has been known for thousands of years, and sounds were believed to improve both body and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 87 publications
1
28
0
Order By: Relevance
“…The decrease in milk yield after being exposed to music may be due to the cows' handling before the milking procedure, which might have distressed them. Mananimal interaction is one of the most common factors that may cause stress to livestock (Ciborowska et al, 2021). In this study, the selected cows had to be fetched, handled, and steered in the right direction for their milking sessions using the AMS, which was different from their normal days before the experiment was conducted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease in milk yield after being exposed to music may be due to the cows' handling before the milking procedure, which might have distressed them. Mananimal interaction is one of the most common factors that may cause stress to livestock (Ciborowska et al, 2021). In this study, the selected cows had to be fetched, handled, and steered in the right direction for their milking sessions using the AMS, which was different from their normal days before the experiment was conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Dairy cattle can pick up frequencies that range from 23 to 35 kHz, which includes some of the ultrasonic range from 16-35 kHz and noises lower than 85 dB (Alworth & Buerkle, 2013;Lemcke et al, 2021). However, it has been reported that cattle exposed to sounds of 80 dB consumed less food, became agitated, and had faster heart rates (Ciborowska et al, 2021;Solan & Józwik, 2009). It could explain why the cows in this study fed less in periods with music, even though the maximum noise audible to cows was 85 dB, as other studies recommended, which was the level applied in this study (Arnold et al, 2007;Lemcke et al, 2021;Weeks et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…One study of dairy cows exposed to auditory stimuli in the form of music detected voluntary approaches by the animals to the milking compartments [ 93 ]. Similarly, Ciborowska et al [ 94 ] stated that certain music genres may function as an environmental stimulus that can relieve the negative effects of stress and pain, improve the heart rate, and reduce anxiety. Genres include classical music, lullabies, and meditation music, all of which can be beneficial for dairy cattle that may be exposed to stressors during milking.…”
Section: Factors That Condition Affecting Milking Capacity In Dairy B...mentioning
confidence: 99%
“…Music for environmental enrichment needs to be carefully selected, and the genre is a significant factor in this choice (Ciborowska et al, 2021) [ 5 ]. Classical music, such as Vivaldi, Bach, and Mozart, relaxing music, and meditation music are most related with health promotion; on the other hand, techno and heavy metal are related to higher stress and heart arrhythmia (Trappe, 2010) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%